Analysis of Information Technology Utilization, Tax Knowledge, and Taxpayer Awareness of the Level of Individual Taxpayer Compliance - Dea Indriyani; Ratu Intan Nur Halimah; Dev Anand (Indonesian Journal of Business Analytics, 2024)
The purpose of this study is to ascertain how information technology utilization affects taxpayer compliance, as well as the effects of tax knowledge and taxpayer awareness on compliance levels. A questionnaire is used to collect primary data for the quantitative research design. A random sampling methodology with one hundred respondents was used to carry out the sampling procedure. Multiple regression data analysis was done using SPSS version 25 software. The study's findings demonstrated that the level of individual taxpayer compliance was significantly impacted by the usage of information technology, tax knowledge, and taxpayer awareness. Individual taxpayer compliance was also significantly impacted by tax knowledge.